Lightweight Version for Digital Quran Model by Handling Duplication - Ashraf Saleh Mohammad Alomoush; Norita Md Norwawi (Research Management Center (RMC), Universiti Teknologi Malaysia (UTM), 2024)
PERINTIS eJournal Vol. 13, No.1(page: 69-76)